2019
DOI: 10.3399/bjgpopen19x101671
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the mental wellbeing of next generation general practitioners: a cross-sectional survey

Abstract: BackgroundFuture and practising GPs encounter various stressors, which can potentially impair mental wellbeing and develop into mental illnesses.AimTo assess mental wellbeing of young and future GPs by their level of training.Design & settingA cross-sectional anonymous survey of members of the Swiss Young General Practitioners Association (JHaS) was undertaken.MethodBasic characteristics and the current mental wellbeing were assessed using the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS). Specific str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…Our survey may have addressed and activated more students with an affinity to human medicine than other students. Third, three quarters of the respondents were young women, an overrepresentation that is often found in similar surveys [2,55]. We have taken account of this by looking at certain gender differences.…”
Section: Limitation and Strengthsmentioning
confidence: 94%
“…Our survey may have addressed and activated more students with an affinity to human medicine than other students. Third, three quarters of the respondents were young women, an overrepresentation that is often found in similar surveys [2,55]. We have taken account of this by looking at certain gender differences.…”
Section: Limitation and Strengthsmentioning
confidence: 94%
“…To the best of the authors' knowledge, there were no studies on residents' perceptions of workload and organizational support in OOH FM in Croatia. However, a recent Swiss study reported that residents in general practice "… indicated not having enough time for a private life", they also had higher risk of burnout, and lower mental wellbeing in comparison to physicians (22). Comparing SAQ sub-scales, all job position groups assessed teamwork climate with the highest average scores, and Organization climate with the lowest average scores.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, in 2019, Swiss general medicine residents reported a mean Wellbeing score of 51 (SD = 7.6) which is quite similar to that found in our study. Moreover, Swiss residents reported stress factors such as the lack of time for private life, heavy workload, including administrative work, and high perceived professional demands ( Lindemann et al, 2019 ). Moreover, the prevalence of high psychological distress in BASIL is comparable to the prevalence of depressive symptoms identified in 12% of the French population aged between 25 and 34 ( Hazo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%